ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT BERMASALAH PADA NASABAH KREDIT PD. BPR BANK DAERAH KABUPATEN MADIUN CABANG BOJONEGORO - Siti Zulbiah; Rodhiyah Rodhiyah (Universitas Diponegoro, 2017)
Credit is a high-risk business activities, due to uncollected loans with a variety of reasons covering, interest rate, term, and sale of the customer that led to a credit crunch in PD. BPR Bank Regency Madiun Branch Bojonegoro. This study aimed to influence interest rate, term, and sale of the customer sales to non-performing loans. Type of explanatory research study with a sample of 74 respondents who experienced a credit crunch. The sampling technique used is saturated samples.Results and discussion: The majority of respondents said that high interest rates, the short term, the sale of non-current customers, and high non-performing loans. There is a positive influence between the interest rates on non-performing loans, with a regression coefficient 0.329. Any negative effects between periods against problem loans, with a regression coefficient -0.314. Any negative effects of the sale of the customer against problem loans, with a regression coefficient -0.641. No effect of interest rate, term, and customer sales results against problem loans, the interest rate regression coefficient 0.136, regression coefficient -0.278 period, and the regression coefficient customer sales results -0.517. With the contribution of independent variables on the dependent variable of 37.8%.Conclusions and suggestions, there is a positive influence between the interest rate on credit problems, there is a negative effect between period and the sale of customers' credit crunch. It is suggested that interest rates more competitively with other banks, provide a more comparable time period, and in doing credit analysis is more emphasis on customers' financial resources.